Current Insights into Various In Vitro Dihaploidization Techniques Used in Brassica Oil Crops - Pavla Bryxová; Eloy Fernández-Cusimamani; Miroslav Klíma (Agronomy)
Brassicas are considered the third most important source of vegetable oil globally. With the escalating production of Brassica varieties, there is growing demand for high-yielding genotypes. Doubled haploid (DH) techniques have become very popular in various Brassica breeding programs. Such DH techniques can play a significant role in plant breeding by accelerating the production of homozygous lines and increasing selection efficiency. Among these methods, isolated microspore culture stands out as the most effective, facilitating the generation of a higher number of embryos compared to conventional methods of plant breeding. Different chemical compounds such as herbicides, brassinosteroids, and polyethylene glycol have an antimitotic effect and have been found to generate DH plants and improve microspore embryogenesis in Brassica species. Colchicine and trifluralin have proven to be efficient chromosome-doubling agents as well as important supplements that can increase the rate of embryogenesis. This review serves as a comprehensive summary and effectiveness evaluation of the latest research findings in the Brassica oil crops to help increase efficiency of the future research focusing on DH methods and application of antimitotic agents in the various oilseed species of the genus Brassica.